PENGARUH MODEL PEMBELAJARAN MAKE A MATCH TERHADAP HASIL BELAJAR SISWA KELAS IV TEMA 7 INDAHNYA KEBERAGAMAN DINEGERIKU DI SD NEGERI 091254 BATU ONOM - Yosindi Tamaro Aruan; Rio Parsaoran Napitupulu; Eva Pasaribu (JOURNAL SAINS STUDENT RESEARCH, 2024)
This research aims to investigate the effect of the Make a Match learning model on the learning outcomes of grade 4 students on theme 7 "The Beauty of Diversity in My Country" at SDN 091254 Batu Onom using only the experimental class. The Make a Match learning model is a method that involves students in matching concepts related to the learning topic. The research method used was an experiment with a pre-test post-test control group design. The experimental class consists of one class of 4th grade students who use the Make a Match learning model. Data on student learning outcomes was collected through tests before and after treatment. Data analysis was carried out using statistical tests to see the effect of the Make a Match learning model on student learning outcomes. The alternative hypothesis in this research was accepted which states that there is an influence of the Make a match learning model on the learning outcomes of class IV students. Theme 7 The beauty of diversity in my country in sub-theme I Learning 3 at SD Negeri 091254 Batu Onom for the 2023/2024 academic year. This is proven by the value of tcount > ttable using a significance level of 0.05 and df = 24, namely 1.71088 > 14,199.